2015
DOI: 10.1515/ijme-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth, Exchange Rate and Constrained Competiveness of the Tourism Sector in Andalucía

Abstract: This paper examines the relationship between tourism and economic growth, analyzing key factors affecting tourism income in Andalucía, Spain. Based on time series annual data for the period 2005 to 2012 and a multiple regression analysis we show that international tourism has made an important contribution to Andalucía's economic growth. Some of the factors considered in the analysis include the number of luxury hotels, the hotel price index and the exchange rate, though the latter is outside of the control of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Study results were showed that there was a possible relation between selecting variables. Nasir et al (2015) revealed the association among economic growth and tourism in the determined the liaison between tourism and GDP in the selected the country that was Spain. The data were gathered using time series for the period of 2005 until 2012 and through an analysis of multiple regressions find the fact that tourism from abroad has played significant contributions to the economic growth of Andalucia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Study results were showed that there was a possible relation between selecting variables. Nasir et al (2015) revealed the association among economic growth and tourism in the determined the liaison between tourism and GDP in the selected the country that was Spain. The data were gathered using time series for the period of 2005 until 2012 and through an analysis of multiple regressions find the fact that tourism from abroad has played significant contributions to the economic growth of Andalucia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Irritating behaviour of visitors + Andereck et al, 2005;Byrd et al, 2008;Brida et al, 2011;Gursoy & Rutherford, 2004;McCartney & Weng In, 2016;Ozturk et al, 2015;Page, 2007 Burger et al, 2001;Cheng et al, 2013;Crouch, 1995;De Vita & Kyaw, 2013;Formica, 2006;Kulendran & King, 1997;Kulendran & Witt, 2003;Law et al, 2004;Nasir et al, 2015;Nelson et al, 2011;Peng et al, 2012;Simpson & Siguaw, 2008;Song & Li, 2008;Song & Witt, 2006) Natural and cultural tourism potential…”
Section: Irritation Of Residentsmentioning
confidence: 99%
“…Using the data from Andalusia, Spain between 2005 and 2012 with the Multiple Regression analysis and Least Squares method, Nasir et al (2015), concluded that the real exchange rate, the number of international tourists, hotel prices and the number of star hotels are important factors affecting tourism revenues.…”
Section: Literature Reviewmentioning
confidence: 99%